Spatial analysis of historical extreme rainfall characteristics using regionalization in the Lake Biwa and Yodo River Basin, Japan. Issue 3 (3rd March 2023) - Yazawa, Taishi; Shoji, Ayane
Abstract: This research investigated the historical changes in basin-scale rainfall characteristics and their spatial distributions in the Lake Biwa and Yodo River Basin. Nine rainfall indices including two general and seven extreme rainfall indices and the probable rainfall according to 50- and 100-year return periods were evaluated based on the data gathered from 61 rain gauge stations. The regionalization of the rainfall indices and probable rainfall was then examined using spatial interpolation via the Kriging method. The results of the spatial analysis for the rainfall indices showed that there is a potentially high risk of extreme rainfall events and pluvial floods, particularly in the northern, western, and southern areas. The 50- and 100-year probable rainfall has historically increased in the north through to the western area of the basin. The return periods of the 50- and 100-year rainfall events decreased in the northern area of Lake Biwa and the western area of the basin. The findings of this research suggest that the local flood management plan needs to be updated depending on the regional differences in extreme rainfall characteristics. In basins/areas with sparsely distributed rain gauge stations, regionalization can provide useful information as part of local flood management planning. HIGHLIGHTS: Regionalization of the historical extreme rainfall characteristics was conducted. Northern, western, and southern areas have a potentially high risk of extreme rainfall events. Return periods of specific rainfall events decreased in the northern area and the western area of the basin. Local flood management planning needs to be updated with the understanding of regional differences in rainfall characteristics. Graphical Abstract